2015
DOI: 10.1371/journal.pone.0121347
|View full text |Cite
|
Sign up to set email alerts
|

Jumping to Conclusions Style along the Continuum of Delusions: Delusion-Prone Individuals Are Not Hastier in Decision Making than Healthy Individuals

Abstract: Literature comparing ‘jumping to conclusions’ (JTC) between patients and healthy controls has demonstrated the importance of the reasoning bias in the development of delusions. When groups that vary along the entire delusional continuum are included, the relationship between JTC and delusionality is less clear. This study compared JTC and delusional dimensions between 28 patients with delusions, 35 delusion-prone individuals and 32 non-delusion-prone individuals. Delusion proneness was defined by an establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
2
10
3
Order By: Relevance
“…JTC and BIB did not correlate with the overall frequency of DLEs. The lack of relationship between JTC and DLEs has, however, already been detected in previous studies among healthy individuals [51,52], and is consistent with the suggestion that JTC is more closely related to clinically relevant delusions than to delusion-like experiences [20,53]. Similarly, some previous studies also demonstrated the lack of correlation between BIB and overall frequency of DLEs measured by PDI [21].…”
Section: Discussionsupporting
confidence: 89%
“…JTC and BIB did not correlate with the overall frequency of DLEs. The lack of relationship between JTC and DLEs has, however, already been detected in previous studies among healthy individuals [51,52], and is consistent with the suggestion that JTC is more closely related to clinically relevant delusions than to delusion-like experiences [20,53]. Similarly, some previous studies also demonstrated the lack of correlation between BIB and overall frequency of DLEs measured by PDI [21].…”
Section: Discussionsupporting
confidence: 89%
“…A departure from the literature is that our tasks were not correlated with the PDI, which is associated with jumping to conclusions in clinical ( Peters et al., 1999 , 2004 ) and non-clinical ( Colbert and Peters, 2002 ; So and Kwok, 2015 ) groups ( Ross et al., 2015 ). However, this is not universally consistent, as other studies have not found correlations between the PDI and DTD ( Lincoln, 2010 ; Ziegler et al., 2008 ).…”
Section: Discussioncontrasting
confidence: 68%
“…The proportion of participants who answered affirmatively to seven or more items of the PDI-21was higher in this study than in that of Fonseca-Pedrero, Paino, Santarén-Rosell and Lemos Giráldez (2012) which was also conducted with university students. Other studies, such as that by So and Kwok (2015), found higher overall scores in non-clinical participants in the PDI-21 than those obtained in our study.…”
Section: Discussioncontrasting
confidence: 61%